2009
DOI: 10.1177/107327480901600107
|View full text |Cite
|
Sign up to set email alerts
|

Non-Endometrioid Adenocarcinoma of the Uterine Corpus: A Review of Selected Histological Subtypes

Abstract: UPSC and CC are managed similarly since sufficient data to separate treatment recommendations are lacking. Because both histologies are associated with a high rate of recurrence, adjuvant therapy is recommended even in women with early-stage disease. The remaining cell types should be treated similar to endometrioid or other low-grade histologies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
93
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(100 citation statements)
references
References 50 publications
3
93
0
4
Order By: Relevance
“…Our data confirm that even in a selected cohort of high-risk patients serous and clear cell histology portends poor prognosis when compared with endometrioid tumors. 28 However, even after exclusion of the non-endometrioid tumors, molecular analysis can discriminate patients with a good and poor prognosis. Importantly, our analyses further support previous studies that showed an association of POLE proofreading mutations with younger age and favorable prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Our data confirm that even in a selected cohort of high-risk patients serous and clear cell histology portends poor prognosis when compared with endometrioid tumors. 28 However, even after exclusion of the non-endometrioid tumors, molecular analysis can discriminate patients with a good and poor prognosis. Importantly, our analyses further support previous studies that showed an association of POLE proofreading mutations with younger age and favorable prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Topographic and morphologic data were coded according to the International Classification of Diseases for Oncology (ICD-O), 2nd [26] or 3rd [27] edition. Using these codes, we classified endometrial cancer into type I or type II (Table 1), based on prior literature [16][17][18][19][20] and systematic review of the ICD-O codes by the authors (SU and AM).…”
Section: Methods Study Population and Dietary Assessmentmentioning
confidence: 99%
“…From a molecular point of view, type II endometrial cancer is often associated with p53 mutations, which commonly lead to DNA derangement, chromosomal instability and a more aggressive clinical behavior [17]. Women affected by type II cancers have a higher incidence of advanced-stage disease at diagnosis, a marked tendency to recurrence, and consequently a worse prognosis [18]. Further, uterine carcinosarcoma and type II endometrial cancers share similar molecular characteristics [19] and have similar clinical outcomes [20].…”
Section: Introductionmentioning
confidence: 99%
“…In support of extensive prior clinical and incidence surveys, we also found that Type II tumors are diagnosed more often among older and non-white women [8,[15][16][17][18][19][20]. These differences in risk factor relationships, in combination with the more frequent occurrence of Type II cancers after menopause, provide some of the strongest epidemiologic support that endometrial cancers are etiologically heterogeneous.…”
Section: Discussionmentioning
confidence: 55%